Designer rice: New concept for climate change - Chaudhari, Prabha R; Sharma, Bhawana; Parikh, Mangla; Sharma, Deepak (Recent Research in Science and Technology, 2014)
<!--[if gte mso 9]> Normal 0 false false false EN-US X-NONE X-NONE MicrosoftInternetExplorer4 <![endif]--> Rice is the most important cereal crop that has been referred as global grain because of its use as prime staple food in about 100 countries of the world. Chhattisgarh popularly known as ‘Rice Bowl of India’. The rising demand saturation of cultivable field and climate change cause a supply shortage of a crop in the near future. The impact of climate change has serious implications for productivity and production of crops, thus threatening our food security and health and livelihood of millions. By the near 2025, about 785 million tonnes of paddy which is 70% more than the current production is needed to meet the growing demand. To achieve the expected yield and hike the productivity of rice, it becomes necessary to design rice according to change climate. The newly designed plant type was mainly based on the results of simulation modeling and new traits were mostly morphological. The proposed new plant type has low tillering capacity, few unproductive tillers, more filled grains per panicle, plant height of 90-100 cm, thick and sturdy stems, leaves that are thick, dark green and erect, a vigorous root system, 100-135 days crop duration and increased harvest index. Therefore, there is an urgent need for the development of designer varieties to sustain and enhance the productivity and production of agricultural crops even in changing climate regimes. <!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <![endif]-->